Comparative Clinical Study between Sealants and Preventive Resin Restorations (PRR) On First Permanent Molar in Children. (Journal of Hama University, 2019)
The purpose of this study is to compare the clinical success between preventive resin restoration, and pit and fissure sealant in terms of retention and caries prevention on first permanent molars. Sealants(Helioseal F) and (Tetric Flow) used in preventive resin restorations(PRR) were applied to first permanent molars in 36 children 6.6-8.6 years old. We divided them randomly into four groups of 36 teeth each, according to application technique (sealant placement using standard procedures \ sealants with bonding agent \ PRR \control group). It was independently evaluated in terms of retention and the presence of caries at 4 , 9 months.PRR showed complete retention were %97,2, %86,1 at 4 , 9 months application, respectively, while Helioseal F retention rates were %88,9 , %52,8 respectively, and Helioseal F with bonding agent retention rates were %91,7, %63,9 respectively for the same evaluation periods.The retention rate of PRR was significantly higher among all materials tested(P0.05).These results suggest that preventive resin restorations restored with flowable composites are helpful in terms of retention and caries reduction.